XI Congresso Nazionale Oggetti Compatti – CNOC XI - Amato, Elena; Bucciantini, Niccolò; Olmi, Barbara (Il Colle di Galileo, 2020)
The 11th edition of the biennial national workshop on the physics of compact objects, “CNOC XI”, was held at the Department of Physics and Astronomy of the University of Florence. Workshops of this series have always intended to bring together the Italian community interested in scientific topics related to the astrophysics of compact objects: neutron stars, black holes, and white dwarfs. In recent times, the detection of gravitational waves and very high energy neutrinos has motivated the addition of multi-messenger astronomy as an important, rapidly growing subfield. The final part of the workshop has traditionally been devoted to the discussion of upcoming observational facilities and brainstorming on the science which they will make possible.